Pengaruh Jumlah Uang Beredar, Pengeluaran Pemerintah, dan Suku Bunga terhadap Tingkat Inflasi di Nanggroe Aceh Darussalam - Rahmawati - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this study is to investigate and analyze the influence of money supply, government spending, and interest rate of the inflation rate in Nanggroe Aceh Darussalam. In the analysis used multiple linear regression analysis (Multiple Regressions). This study uses time series data starting from 1980 to 2006. The type of data is secondary data obtained from the Central Statistics Agency, the Regional Capital Investment Coordinating Board (BKPMD), Bank Indonesia, and other related intansi and from various sources and other literature in connection with this research. Data were analyzed with OLS approach (Ordinary Least Square).The estimation results show satisfactory results. This is evident both from the testing of universal and partial, in which all independent variables in this study have a significant effect on inflation. Based on estimates of the variables in the money supply and government spending have positive and significantly and interest rates and also significantly negative effect on inflation. Based on estimates obtained koefiien determinant (R2) of 0.6878 which means that 68.78% variation of the variable inflation can be explained by variables in the money supply, government spending and interest rate of 68.78 percent and the balance of 31.22% is explained by variables which are not included in this study. In reducing inflation in Nanggroe Aceh Darussalam, the government can do by way of raising the level of production, lower wage levels and to supervise the rising prices of basic needs.Keywords: Inflation Analysis